THE USE OF PANTOMIME VIDEO IN TEACHING WRITING OF DESCRIPTIVE TEXT IN SMAN 1 SIANTAN - Deta, Maria; Sutapa, Gatot; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe objective of the study was to find out whether or not the use of pantomime video can increase the students’ descriptive text writing achievement. The data was collected and analyzed with the non-equivalent control group design. Based on the test result, the writer discovered a good result that was shown by the effect size which was 1.24 and it was qualified as strong effect. In this case, the use of pantomime video can attract the students’ attention in learning descriptive text writing. The students know how to organize their ideas and state that ideas on a paper. In conclusion, the use of pantomime video to the Tenth Grade Students of SMA Negeri 1 Siantan in Academic Year 2016/2017 can increase their descriptive text writing achievement with strong effect. Keywords: Pantomime Video, Teaching Writing, Descriptive Text